One year follow-up of the changes of the nasal cavity morphology induced by rapid maxillary expansion. a study on 3-D computed tomography models - Özkaya, Selin (My University, 2009)
2. ÖZET Burun boşluğu morfolojisinde hızlı üstçene genişletmesiyle oluşan değişikliklerin bir sene sonraki kalıcılığının 3-boyutlu tomografi ile değerlendirilmesi . Bu çalışmada Hızlı Üstçene Genişletmesi (HÜG) sonrası bir senelik pekiştirme dönemini tamamlamış hastalarda, burun boşluğundaki değişikliklerin kalıcılığı, bilgisayarlı tomografi alınarak oluşturulan üçboyutlu veriler incelenerek değerlendirilmiştir. Çalışma grubu Marmara Üniversitesi Dişhekimliği Fakültesi Ortodonti nden seçilen 24 hastadan oluşmaktadır. Çalışmaya dahil edilen hastalar 11-17 yaşlarında, transvers yönde maxiller darlık ve çift taraflı yan çapraz kapanış göstermektedirler. Tüm hastalarda HÜG prosedürü akrilik splint tipi Hyrax apareyiyle yapılmıştır. Genişletme öncesinde, aktif genişletmeden sonra 3 aylık pekiştirme dönemi sonunda ve pekiştirme dönemininin bitiminden bir sene sonra rutin ortodontik kayıtlarla beraber aksiyel tomografiler alınmıştır. Tomografiler değerlendirilip, 3-boyutlu görüntüleme ve hastaların nazal kavitenin total hacminin hesaplanması için Materialise Medical Co. tarafından çıkarılmış olan Mimics 10.11 programıyla analiz edilmiştir. Veriler değerlendirildikten sonra, expansiyon öncesi, sonrası ve bir sene sonraki sonuçlar arasında istatiksel önemi olan farklılıklar görülmüştür. HÜG sonrası 3 aylık pekiştirme dönemi sonunda, HÜG öncesine gore istatistiksel önemi olan % 10.6’lük bir artış görülmüştür. HÜG sonrası üç aylık pekiştirme döneminden bir sene sonra alınan kayıtlar bu artışın istatistiksel önemi olan bir azalma gösterdiğini ortaya koyuyor, fakat HÜG öncesi değerlere kıyasla halen istatistiksel önemi olan 4 % ‘lik bir artışın kalıcığını koruduğunu gösteriyor. Hızlı üstçene genişletmesi, nazal kavite, nazal hacim, intranazal kapasite, bilgisayarlı tomografi, pekiştirme 1.

The purpose of this study is to evaluate the permanence of the changes in the nasal cavity induced by rapid maxillary expansion (RME) one year after the completion of the retention period using 3-D models obtained from computed tomographies (CT). The study involved a group of 27 patients treated at the Department of Orthodontics of the Dental Faculty of Marmara University. The patients included in this study were from 11 to 17 years old, and presented with transverse maxillary deficiency and bilateral posterior crossbite. In all patients RME procedure was carried out with an acrylic cap splint type Hyrax appliance. Routine orthodontic records as well as axial tomograms were obtained before expansion, at the end of the 3-month retention period after active expansion was completed, and one year after the retention period. Tomograms were assessed and analyzed by Mimics 10.11 computer software launched by Materialise Medical Co. in order to reconstruct 3-dimensional images and calculate the total volume of the nasal cavities of the patients. After examining the data, a significant difference was found between the pre-expansion, post- expansion and after one year measurements. There was a significant increase of 10.6 % in the volume of the nasal cavity due to RME as measured at the end of 3-months retention period. However follow-up results after 1 year showed, that there was a significant decrease in the volume of the nasal cavity comparing to the post-expansion measurements. Nevertheless, when compared to the pre-expansion values there was still a significant 4 % increase in the volume of the nasal cavity 1 year after RME. Key words: Rapid maxillary expansion, nasal cavity, nasal volume, intranasal capacity, computed tomography, retention
Keywords: Ağız ve Diş Sağlığı; Bilgisayarlı Tomografi; Ortodonti; Tıp